UMP announcement system via GSM - Norsuhada, Khosni (2011)
Nowadays,there are many methods in broadcasting an announcement throughout an organization.In Universiti Malaysia Pahang (UMP),announcements are sent to the community by using the posting on the announcement board around the faculty building and also using the e-community website UMP Portal.However,announcement through UMP website portal is less optimize uses.This is because a networking system at UMP is frequently down.Thus,the announcements cannot be read.In addition,majority of UMP communities rarely open UMP Portal.Therefore,they missed to read announcement on the UMP Portal.To overcome this problem, an UMP Announcement System via GSM has been developed. The alternative of GSM network is application in order to relay the announcement.The application Global System for Mobile Communication (GSM),in supporting the announcement sending from computer and receiving on the mobile phone.